Access to Credit Loans and Firm-level Productivity of Philippine Manufacturing Firms: An Endogenous Switching Approach - Catacutan, Zandro M. (Animo Repository, 2024)
Numerous studies have shown that financial development, such as access to credit loans, has a positive effect on firmlevel productivity. However, the relationship between financial development and productivity remains an area of interest because positive effects should at least be accompanied by evidence of the absence or presence of both heterogeneity and selection bias effects. We examine this relation using extensive cross-sectional data from the World Bank Enterprise Survey of firms with access to credit loans and firms without access to credit loans. We employ instrumental variables regression and endogenous switching regression approach to test for selection bias from firms’ participation and non-participation in credit loans and its impact on firm-level productivity and predict counterfactual productivity changes relative to access to credit loans and non-access to credit loans. We find evidence of productivity differences between the two groups of firms. Results under counterfactual predictions show productivity premium for firms with access to credit loans but not for firms that did not access credit loans. In sum, our results suggest a careful broadening of access to financial products and services.